Revision Microvascular Decompression for Trigeminal Neuralgia and Hemifacial Spasm: Factors Associated with Surgical Failure - Ravina, Kristine; Strickland, Ben A.; Rennert, Robert C.; Bakhsheshian, Joshua; Russin, Jonathan J.; Giannotta, Steven L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective To investigate risk factors for symptom recurrence in patients requiring a revision microvascular decompression (MVD) for trigeminal neuralgia (TN) or hemifacial spasm (HFS).Design Retrospective review of a prospectively maintained database.Participants Seventeen consecutive patients undergoing revision MVD at our institution between January 1993 and September 2017.Main Outcome Measures The incidence and causes for revision MVDs were recorded. Response to revision MVD for TN was tracked using the Barrow Neurological Institute (BNI) grading scale. Response to revision MVD for HFS was graded as “no improvement,” “some relief,” or “complete resolution” of symptoms.Results Revision MVD rate for the senior author across all MVDs performed in this period was 1.9% for TN and 9.3% for HFS. Initial MVD failure was primarily caused by active inflammation and/or scarring and adhesions in 5/17 patients, malposition/slippage of Teflon in 3/17 patients, and insufficient Teflon in 1/17 patients. Without other factors, a new site of neurovascular conflict was identified in 4/17 patients, while the same site of neurovascular conflict was found in 3/17 patients. No cause could be identified in 1/17 patients. Scarring was found primarily in the TN group and was associated with symptom persistence.Conclusion Revision MVD for recurrent TN and HFS is an effective procedure offering the prospect of a complete cure. Proper Teflon use is crucial for surgical success. Scarring after initial MVD is a negative prognostic factor requiring destructive treatment consideration. Although morbidity rates were slightly increased with revision versus original MVDs, the complications were non-disabling and resolved over time.
Keywords: hemifacial spasm; microvascular decompression; neurovascular conflict; reoperation; trigeminal neuralgia